Léger and Purist Paris. (London : The Tate Gallery, 1970)
Léger, Fernand ; Archipenko, Alexander ; Baumeister, Willi ; Braque, Georges ; Buchet, Gustave ; Cahn, Marcelle ; Csaky, Josef ; Delaunay, Robert ; Gris, Juan ; Herbin, Auguste ; Lipchitz, Jacques ; etc.
Léger and Purist Paris, The Tate Gallery, London, 18 November 1970 - 24 January 1971
boek